2019
DOI: 10.1080/07373937.2019.1645685
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted drying of orange peel in atmospheric freeze-dryer and convective dryer operated at moderate temperature

Abstract: Atmospheric freeze-drying (AFD) at -10 °C and moderate temperature convective drying (MTD) at 50 °C without and with ultrasound application (20.5kW/m ) were carried out. Alcohol insoluble residue (AIR) and its swelling capacity (SC), water retention capacity (WRC) and fat retention capacity (FRC) were measured in the dried product. Ultrasound significantly shortened the drying time in both processes, the intensification effect being more significant in atmospheric freeze-drying (57 % and 27 % reduction in atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
(43 reference statements)
3
7
1
Order By: Relevance
“…A similar value of 67.2 % was reported by Kosmala et al (2011) . This value was lower than that obtained by Borsini et al (2021) for artichoke bracts (85 %), but higher than that of artichoke stems (63 %) or orange peel (53 %) ( Mello et al, 2020 ).
Fig.
…”
Section: Resultscontrasting
confidence: 65%
“…A similar value of 67.2 % was reported by Kosmala et al (2011) . This value was lower than that obtained by Borsini et al (2021) for artichoke bracts (85 %), but higher than that of artichoke stems (63 %) or orange peel (53 %) ( Mello et al, 2020 ).
Fig.
…”
Section: Resultscontrasting
confidence: 65%
“…Therefore, diffusion is the major physical mechanism of mass transfer in the apple samples. The same result was reported in hot air drying of Granny Smith apple (Andres et al, 2004) and ultrasound assisted convective drying of orange peel (Mello et al, 2020). Contreras et al (2008) indicated that the Page and Modified Page models were represented the drying kinetics of apple products better than the other models like our study.…”
Section: B a Csupporting
confidence: 91%
“…As for β parameter, it significantly decreased when ultrasound was applied, which means an increase in the drying kinetics. This fact has been previously observed applying ultrasound in AFD of orange peel [8].…”
Section: Modellingsupporting
confidence: 77%